Regulating Terahertz Photoconductivity in Two-Dimensional Materials - Xiao Xing; Zeyu Zhang; Guohong Ma (Photonics, 2023)
Two-dimensional materials represented by graphene have attracted extensive interest owing to the unique layer-dependent physical properties that are tunable with various external fields. In addition, by stacking two or more 2D materials together, a new material with the desired properties can be tailored and designed. Fully understanding the dynamical photoconductive response in 2D materials is uttermost important to design and develop the advanced optoelectronic devices. Terahertz (THz) time-domain spectroscopy (TDS) and time-resolved THz spectroscopy are powerful spectroscopic tools with the advantages of being contact-free and noninvasive, which have been widely used to study the photoconductivity (PC) of 2D materials. In this review, firstly, we provide a short introduction of the 2D materials and THz spectroscopy, and then a brief introduction of the experimental setup and experimental data analysis based on time-resolved THz spectroscopy are presented. After that, we overview the latest progress on the regulation of the THz PC that includes: (1) regulating the THz PC of graphene (Gr) and transition metal dichalcogenide (TMD) thin films with oxygen adsorption; (2) regulating the THz PC of Gr and Gr/TMDs heterostructures by electric gating and a built-in field introduced by a substrate; (3) regulating the THz PC of Gr/TMD heterostructures via optical gating; and (4) we overview the latest progress on the observation of elementary excitations in 2D materials with THz PC spectra following optical excitation and THz PC regulation via the photoexcitation of quasi-particles. Finally, we conclude the review and present a short overview of future research directions.